Preventing Postpartum Venous Thromboembolism in 2022: A Narrative Review - Blondon, Marc; Skeith, Leslie (Frontiers in Cardiovascular Medicine, 2022)
The postpartum period represents the most critical time for pregnancy-associated venous thromboembolism (VTE), which is responsible for substantial morbidity and an important cause of maternal mortality. The estimated risk of postpartum VTE of about 1/1,000 deliveries can be modulated with the knowledge of maternal and obstetrical risk factors, although a precise estimate remains challenging in individuals. The use of postpartum low-dose low-molecular-weight heparins are tailored at intermediate and high-risk groups to reduce the thrombotic burden, despite the lack of dedicated randomized controlled trials. In this review, we will highlight the contemporary evidence on the risk of postpartum VTE, its stratification and its prevention. We will also discuss our knowledge on the values and preferences of women for postpartum thromboprophylaxis and their adherence to treatment.